Borrelia burgdorferi surface‐located Lmp1 protein processed into region‐specific polypeptides that are critical for microbial persistence. (25th May 2018) - Zhuang, Xuran; Yang, Xiuli; Altieri, Amanda S.; Nelson, Daniel C.; Pal, Utpal
Abstract: One of the Borrelia burgdorferi virulence determinants, annotated as Lmp1, is a surface‐exposed, conserved, and potential multi‐domain protein involved in various functions in spirochete infectivity. Lmp1 contributes to host–pathogen interactions and evasion of host adaptive immunity by spirochetes. Here, we show that in diverse B. burgdorferi species, Lmp1 exists as distinct, region‐specific, and lower molecular mass polypeptides encompassing 1 or more domains, including independent N‐terminal and middle regions and a combined middle and C‐terminal region. These polypeptides originate from complex posttranslational maturation events, partly supported by a periplasmic serine protease termed as BbHtrA. Although spirochete persistence in mice is independently supported by domain‐specific Lmp1 polypeptides, transmission of B. burgdorferi from ticks to mammals requires essential contributions from both N‐terminal and middle regions. Interference with the functions of Lmp1 domains or their complex posttranslational maturation events may aid in development of novel therapeutic strategies to combat infection and transmission of pathogens.